Landscape-scale modelling of agroforestry ecosystems services in Swiss orchards: a methodological approach - Kay, Sonja; Crous-Duran, Josep; García de Jalón, Silvestre; Graves, Anil; Palma, João H. N.; Roces-Díaz, José V.; Szerencsits, Erich; Weibel, Robert; Herzog, Felix (Springer, 2018)
Context Agroforestry systems in temperate Europe are known to provide both, provisioning and regulating ecosystem services (ES). Yet, it is poorly understood how these systems affect ES provision at a landscape scale in contrast to agricultural practises. Objectives This study aimed at developing a novel, spatially explicit model to assess and quantify bundles of provisioning and regulating ES provided by landscapes with and without agroforestry systems and to test the hypothesis that agroforestry landscapes provide higher amounts of regulating ES than landscapes dominated by monocropping. Methods Focussing on ES that are relevant for agroforestry and agricultural practices, we selected six provisioning and regulating ES—“biomass production”, “groundwater recharge”, “nutrient retention”, “soil preservation”, “carbon storage”, “habitat and gene pool protection”. Algorithms for quantifying these services were identified, tested, adapted, and applied in a traditional cherry orchard landscape in Switzerland, as a case study. Eight landscape test sites of 1 km × 1 km, four dominated by agroforestry and four dominated by agriculture, were mapped and used as baseline for the model. Results We found that the provisioning ES, namely the annual biomass yield, was higher in landscape test sites with agriculture, while the regulating ES were better represented in landscape test sites with agroforestry. The differences were found to be statistically significant for the indicators annual biomass yield, groundwater recharge rate, nitrate leaching, annual carbon sequestration, flowering resources, and share of semi-natural habitats. Conclusions This approach provides an example for spatially explicit quantification of provisioning and regulating ES and is suitable for comparing different land use scenarii at landscape scale.
Keywords: Biodiversity; Cherry orchard; Climate change mitigation; Erosion; Landscape water balance; Lonsdorf model; Nitrate leaching